2012
DOI: 10.1210/en.2011-1442
|View full text |Cite
|
Sign up to set email alerts
|

Protection from Palmitate-Induced Mitochondrial DNA Damage Prevents from Mitochondrial Oxidative Stress, Mitochondrial Dysfunction, Apoptosis, and Impaired Insulin Signaling in Rat L6 Skeletal Muscle Cells

Abstract: Saturated free fatty acids have been implicated in the increase of oxidative stress, mitochondrial dysfunction, apoptosis, and insulin resistance seen in type 2 diabetes. The purpose of this study was to determine whether palmitate-induced mitochondrial DNA (mtDNA) damage contributed to increased oxidative stress, mitochondrial dysfunction, apoptosis, impaired insulin signaling, and reduced glucose uptake in skeletal muscle cells. Adenoviral vectors were used to deliver the DNA repair enzyme human 8-oxoguanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
69
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 32 publications
5
69
1
Order By: Relevance
“…We found mtDNA damage after the treatment with palmitate in both myoblasts and myotubes using the QPCR method, which is able to detect a wide range of types of DNA lesions. Our observation is in accordance with another study [18] where mtDNA damage was detected in L6 myotubes exposed to palmitate using quantitative alkaline Southern blot analysis. Authors of this study postulated that mtDNA damage is a critical event leading to mitochondrial dysfunction with consequent increase in oxidative stress and finally to apoptosis [18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found mtDNA damage after the treatment with palmitate in both myoblasts and myotubes using the QPCR method, which is able to detect a wide range of types of DNA lesions. Our observation is in accordance with another study [18] where mtDNA damage was detected in L6 myotubes exposed to palmitate using quantitative alkaline Southern blot analysis. Authors of this study postulated that mtDNA damage is a critical event leading to mitochondrial dysfunction with consequent increase in oxidative stress and finally to apoptosis [18].…”
Section: Discussionsupporting
confidence: 93%
“…Increased oxidative stress associated with some features of mitochondrial dysfunction was reported in skeletal muscle cells after the exposure to palmitate [17,18]. However, the effects of saturated fatty acids on mitochondrial respiration have not been well studied, particularly in undifferentiated skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this time frame, only PKR is phosphorylated in response to ceramide without any change in JNK phosphorylation state, suggesting that ceramide-induced PKR-mediated JNK phosphorylation requires more time (up to 16 h). This is not unprecedented because several studies show that incubation of myotubes from 16 -24 h is necessary to see palmitate or ceramide induce JNK phosphorylation (45)(46)(47)(48). This result confirms previous data demonstrating that, in the short term, ceramide inhibits insulin signaling through the acti-FIGURE 8.…”
Section: Discussionsupporting
confidence: 87%
“…We found that muscle cells incubated with palmitate exhibited a lower OCR than those exposed to palmitoleate alone but that cellular respiration and TAG accumulation was augmented in the presence of both fatty acids together. The reduced oxidative capacity associated with oversupply of SFA is likely to be a consequence of mitochondrial dysfunction given that i ) we observed a reduction in Cox4.1 and PGC1 ␣ (two proteins with important but distinct roles in mitochondrial biology) and ii ) recent studies show that palmitate causes mitochondrial damage/fragmentation in muscle cells by inducing a greater infl ammatory drive, insulin resistance, and apoptosis ( 60,61 ). In contrast, promoting oxidation and/or storage of SFAs by coprovision of MUFAs reduces the proapoptotic drive of palmitate ( 58 ), and as we and others ( 6 ) found, it also suppresses NF B-mediated proinfl ammatory signaling.…”
Section: Discussionmentioning
confidence: 71%